Financing Transit-Oriented Development with Land Values : Adapting Land Value Capture in Developing Countries - Suzuki, Hiroaki (Washington, DC: World Bank, 2015)
Cities in developing countries are experiencing unprecedented urban growth. Unfortunately, this is often accompanied by the negative impacts of sprawl as a result of rapid motorization such as congestion, air pollution, greenhouse gas emissions, inefficient use of energy and time, and unequal accessibility. As these cities are often under severe fiscal constraints, they face great challenges in financing capital-intensive mass transit systems to reverse the course of these negative trends. Development-based land value capture (DBLVC) financing schemes being practiced in Asian megacities like Hong Kong SAR, China, and Tokyo have helped them not only to generate funds for transit investment and operational and maintenance costs but also to promote sustainable urban development through transit-oriented development (TOD).